2010
DOI: 10.1542/peds.2009-3060
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Rapid Influenza Test in Children During the H1N1 2009 Influenza A Outbreak

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Sensitivities of RIDTs have varied widely for the diagnosis of seasonal influenza. Few pediatric-specific data are available on RIDT performance for H1N1 2009 influenza A. WHAT THIS STUDY ADDS:To the best of our knowledge, this is the largest series reported to date of a comparison of RIDT performance to 2 reference standards, viral culture and rRT-PCR, for the detection of influenza A H1N1 2009 in respiratory specimens from pediatric patients. abstract OBJECTIVE: To evaluate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 17 publications
5
25
0
2
Order By: Relevance
“…This is consistent with other studies 5 , 9 that found RIDT sensitivity to be significantly higher in infants and children younger than 2 years than in older children. Although higher sensitivity in younger age groups has been observed in several studies, 3 , 5 , 8 , 9 most of the study subjects were children aged 17 years or younger. Our study examined a broad age spectrum of patients and found that a significant decrease in RIDT sensitivity was associated with increasing age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with other studies 5 , 9 that found RIDT sensitivity to be significantly higher in infants and children younger than 2 years than in older children. Although higher sensitivity in younger age groups has been observed in several studies, 3 , 5 , 8 , 9 most of the study subjects were children aged 17 years or younger. Our study examined a broad age spectrum of patients and found that a significant decrease in RIDT sensitivity was associated with increasing age.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that RIDT sensitivity was correlated with increasing viral titer 2 , 6 , 7 and that higher RIDT sensitivity was found in younger age groups than older groups 3 , 5 , 8 , 9 . However, these studies were conducted either in pediatric patients or with a small sample of older patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O método de diagnóstico de referência para infecção pela influenza H1N1 é realizado por meio de cultura viral, porém é necessário um teste de menor custo, prático para uso e com respostas rápidas para detecção da doença 10 . A infecção por H1N1 é uma doença com novas características clínicas, desconforto respiratório de instalação rápida, infiltração de ambos os campos pulmonares, cursando com hipoxemia severa, distúrbios restritivos e mortalidade elevada 1,3 .…”
Section: Resultsunclassified
“…As crianças foram consideradas como um dos grupos de risco, devido à imaturidade do sistema imunoló-gico 3,7,9 , com tempo de transmissão do vírus maior que dos adultos 9 e ocorrência de surtos institucionais em creches e escolas 6 . Pouco se sabe sobre como a circulação do vírus influenza H1N1 afeta a população infantil, uma vez que há escassez de estudos 7,10 . As estratégias de enfrentamento inicial dessa epidemia global foi baseada em medidas de contenção por meio de identificação precoce, tratamento e isolamento de casos e no seguimento de seus contatos próximos 3,6 .…”
Section: Introductionunclassified